مسجد الرحمة بالبياضة ودوره الدعوي والتعليمي - قويدري مروة (University of Eloued جامعة الوادي, 2024)
"للمساجد دور مهم في حياة المسلمين، فهو شعار المسلمين في حياتهم ونبراس مناهجهم، وهذه الدراسة تتحدث عن بيت من بيوت الله عزّ وجل وهو مسجد الرحمة، المسجد العتيق في بلدية البياضة بولاية الوادي بالجنوب الجزائري، تحت عنوان ""مسجد الرحمة بالبياضة ودوره الدعوي والتعليمي"". تهدف هذه الدراسة إلى تقييم الدور الدعوي والتعليمي لمسجد الرحمة، من خلال طرح الإشكالية المتمثلة في: ما هو الدور الدعوي والتعليمي الذي قدمه مسجد الرحمة وما مدى قيامه بالوظائف المنوطة به؟ وللإجابة على الإشكالية اعتمدت على المقابلة كأداة أساسية في البحث والملاحظة كأداة مساعدة. ويحتل المسجد وسط بلدية البياضة، وقد تأسس في القرن17م، وتمّ تجديده أربع مرات آخرها عام1992، وتداول على خدمته الكثير من الأئمة والوعّاظ والمؤذنين والمدرسين، حيث قاموا بدورهم عبر نشاطات عديدة ومتنوعة منذ إنشاء المسجد، وقد كان له دور مقبول في الجانب الدعوي والتعليمي خاصة بعد انتشار الصحوة الإسلامية في ثمانينيات القرن الماضي، مما ساهم في نشر الدعوة إلى الله وإفادة المجتمع وأفراده.""Mosques have an important role in the lives of Muslims, as they are the emblem of Muslims in their lives and the beacon of their curricula. This study talks about one of the houses of God Almighty, which is the Al-Rahma Mosque, the ancient mosque in the municipality of Al-Bayada in the El Oued Province in southern Algeria, under the title “The Preaching and Educational Role of the Al-Rahma Mosque”. This study aims to evaluate the preaching and educational role of Al-Rahma Mosque, by raising the problem of: What is the preaching and educational role provided by Al-Rahma Mosque and the extent to which it fulfills the functions assigned to it? To answer the problem, I relied on the interview as a basic tool in research and observation as an auxiliary tool The mosque occupies the center of the municipality of Al-Bayada. It was founded in the 17th century AD, and was renovated four times, most recently in 1992. Many imams, preachers, muezzins, and teachers took part in its service, as they played their role through many and varied activities since the establishment of the mosque. It has had an acceptable role in the advocacy and educational aspects, especially after The spread of the Islamic awakening in the 1980s, which contributed to spreading the call to God and benefiting society and its individuals
Keywords: المساجد، مسجد الرحمة، الدور الدعوي، الدور التعليمي.; Mosques; Al-Rahma Mosque; advocacy role; educational role.